PENTINGNYA TEORI AKUNTANSI SYARI`AH: PERSPEKTIF AKUNTANSI SOSIAL DAN PERTANGGUNGJAWABAN BISNIS SYARIAH - Hendrarto Widodo (Jurnal Manajemen dan Kewirausahaan, 2016)
This paper discusses the Islamic perspective of accounting, known as sharia accounting. The accounting sharia based on the Qur'an and Hadith, both on paradigms and practices. It is not only a social orientation but also the orientation of the responsibility. The accounting sharia will report the social impacts of an activity and responsibility of humanistic, emancipatory, transcendental and theological. In Islamic terminology, accounting sharia is zakat and amanah oriented.